Legal Protection for Injured Parties in Goods and Services Procurement Agreements - Alifa, Alifa; Sudirman, Maman; Djaja, Benny (Civiliza Publishing, 2025)
The procurement of products and services is an important component of economic activities, both in the public and private sectors. Nevertheless, in practice, legal complications often arise, which can hinder the progress of the project and result in financial losses for all parties. Administrative errors, violations of the law, and differences in contract interpretation that result in disputes are some of them. The purpose of this study is to investigate the legal protections afforded to aggrieved parties in procurement agreements. The expected result is a reduced risk of disputes and increased transparency and effectiveness in the procurement process through an understanding of the legal aspects that govern procurement. Legal protection in disputes over the procurement of goods and services was analyzed using a qualitative method with an analytical descriptive approach in this study. Data was collected from primary legal sources, including statutes, regulations, and court rulings, as well as secondary sources, including academic journals, books, and research reports. The findings of the study show that the procurement of goods and services still faces a range of challenges, including regulatory uncertainty and less transparent practices, which hinder legal protection. Therefore, the mechanism for procurement of goods and services needs to be improved to increase effectiveness and fairness in resolving disputes.